2011
DOI: 10.1063/1.3597228
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligned metal source/drain InP n-metal-oxide-semiconductor field-effect transistors using Ni–InP metallic alloy

Abstract: In this work, we report that a Ni–InP alloy can be used as a source/drain (S/D) metal for InP metal-oxide-semiconductor field-effect transistors (MOSFETs), allowing us to employ the salicidelike self-align S/D formation. Ni–InP alloys have low sheet resistance under 100 Ω/◻ and Ni can be selectively etched without etching of Ni–InP. We also demonstrate operation of the metal S/D InP MOSFETs using Ni–InP alloy. The InP MOSFETs exhibit high Ion/Ioff ratio of 106 and low subthreshold swing of 101 mV/dec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 11 publications
4
41
0
Order By: Relevance
“…Recently, we have found that a Ni-InGaAs alloy formed by direct reaction of Ni and InGaA is one of the materials allowing us to fabricated self-aligned metal S/D structures for InGaAs MOSFETs [28][29][30]. We have also confirmed that the same process is applicable to InP [31]. [28,29] The sheet resistance of the Ni-InGaAs alloy layers, formed by direct reaction of Ni and InGaAs, was determined by TLM patterns on p-InGaAs (1×10 16 cm -3 ).…”
Section: S/d Formationsupporting
confidence: 66%
“…Recently, we have found that a Ni-InGaAs alloy formed by direct reaction of Ni and InGaA is one of the materials allowing us to fabricated self-aligned metal S/D structures for InGaAs MOSFETs [28][29][30]. We have also confirmed that the same process is applicable to InP [31]. [28,29] The sheet resistance of the Ni-InGaAs alloy layers, formed by direct reaction of Ni and InGaAs, was determined by TLM patterns on p-InGaAs (1×10 16 cm -3 ).…”
Section: S/d Formationsupporting
confidence: 66%
“…A possible reason for roughened surface would be related to the phase change and lattice constant change with annealing temperature [43]. Sequential annealing at high temperature after first annealing at low temperature may be helpful to alleviate morphology issue as one can see from silicide and Ni-InP technologies [17], but it seems to be not so effective for Ni-InGaAs system [18].…”
Section: Thermally Stable Contact Design With a Low Specific Conmentioning
confidence: 99%
“…Another alternative to highly doped S/D regions is the use of metal S/D structure for III–V MOSFETs, and has been successfully explored in recent years. For InP channel MOSFETs, Ni–InP alloy S/D has been demonstrated to be very promising with low sheet resistance compared to n+ doped InP S/D and low Schottky barrier height (), analogous to Ni–InGaAs S/D for InGaAs MOSFETs (). It is interesting to note that some works have reported inherent benefits with InP source and/or drains for analog applications.…”
Section: Inp Device Performancementioning
confidence: 99%